THE IMPACTS OF THE FEMALE CHARACTER’S ACTIONS IN THE KOREAN DRAMA ITAEWON CLASS SEEN THROUGH LIBERAL FEMINISM - Inge Shafa Sekarningrum; Teguh Kasprabowo (Universitas Stikubank (UNISBANK) Semarang, 2023)
This research examines liberal feminism of Itaewon Class Korean drama. The study aims to analyze Jo Yi-seo’s struggles portrayed in liberal feminism and the challenges she has to face to reach her dreams. The data derived from Itaewon Class Korean drama were analyzed qualitatively. Itaewon Class (2020) is talking about a young girl named Jo Yi-seo who wants to become a DanBam bar-restaurant manager and make DanBam has customers. However, many people disbelief her values, and she proves to them that she has the potential to make DanBam become popular and has many franchises. The analysis results show how Jo Yi-seo struggles to face the stereotype of being a woman, fight that a woman is not a man’s game, deal with her mother’s expectations, and deal with people who have power. It also shows that Jo Yi-seo is not only independent and brave, but she dares to fight inequity in the social sphere and law. She proves it by her fearlessness when she sees her friend get bullied by a powerful gang girl and when she is being pushed over people’s dominion. Her persistence makes her succeed in reaching what she wants. Keywords: Liberal Feminism, Korean Drama, Motivation, Itaewon Class